Agreement between data obtained from repeated interviews with a six-years interval Concordância entre dados obtidos em entrevistas repetidas com seis anos de intervalo - Carolina Castro Martins; Maria Letícia Ramos-Jorge; Jaime Aparecido Cury; Isabela Almeida Pordeus; Saul Martins Paiva (Universidade de São Paulo, 2008)
The objective of the study was to compare information collected through face-to-face interviews at first time and six years later in a city of Southeastern Brazil. In 1998, 32 mothers (N=32) of children aged 20 to 30 months answered a face-to-face interview with structured questions regarding their children's brushing habits. Six years later this same interview was repeated with the same mothers. Both interviews were compared for overall agreement, kappa and weighted kappa. Overall agreement between both interviews varied from 41 to 96%. Kappa values ranged from 0.00 to 0.65 (very bad to good) without any significant differences. The results showed lack of agreement when the same interview is conducted six years later, showing that the recall bias can be a methodological problem of interviews. O objetivo do estudo foi comparar a informação coletada em entrevista pessoal num primeiro momento e seis anos depois, em Minas Gerais. Em 1998, 32 mães (N=32) de crianças com idade entre 20 a 30 meses responderam à entrevista pessoal com questões estruturadas sobre os hábitos de escovação das crianças, sendo repetida seis anos depois. As duas entrevistas foram comparadas em concordância geral e em coeficientes kappa e kappa ponderado. A concordância geral entre as entrevistas variou de 41% a 96%. Os valores de kappa variaram de 0,00 a 0,65 (muito ruim a bom), sem diferença significativa. Os resultados mostraram que houve ausência de concordância quando a mesma entrevista foi conduzida seis anos depois, mostrando que o viés de memória pode ser um problema metodológico das entrevistas.